Whistleblownig Dan Pengaduan Masyarakat Pendeteksian Serta Pencegahan Fraud BPK DIY - Rizqi Akbar Romadhoni (Universitas Sains dan Teknologi Komputer, 2023)
This research aimed to determine whistleblowing methods' effectiveness and public complaints in detecting and preventing fraud at BPK DIY Representative. This research used the interview method. The data that has been obtained will be processed using descriptive analysis techniques with a qualitative approach. The findings of this research show that the whistleblowing and public complaints method has a qualified design to provide facilities for whistleblowers to report fraud actions. All information from the whistleblowing method is very important as an early indication in detecting fraud. However, in its implementation of whistleblowing and community complaints, it has not run optimally.